2015
DOI: 10.1179/1362171815y.0000000055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of current on nanoparticle reinforced magnesium alloy welding joints

Abstract: Effects of welding current on macromorphologies, microstructures and mechanical properties of nano-SiC particles strengthening activating flux tungsten inert gas welded AZ31 magnesium alloy joints were investigated by scanning electron microscope and energy dispersive X-ray spectrometer observations and microhardness and tensile tests. The results showed that SiC particles mainly dwelled in the centre and bottom zone of welding pool. Moreover, with the welding current increasing, the mechanical properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Figure 21 shows the velocity field distribution of the cross-section of the molten pool perpendicular to the welding direction during A-TIG welding of dissimilar magnesium alloys AZ61 and AM60. According to the studies of Xie et al [ 24 ] and Wu et al [ 25 ], during A-TIG welding with activating flux, the increase of penetration depth is mainly due to the influence of surface tension. Furthermore, the positive and negative temperature gradient has a great impact on the depth of the molten pool.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 21 shows the velocity field distribution of the cross-section of the molten pool perpendicular to the welding direction during A-TIG welding of dissimilar magnesium alloys AZ61 and AM60. According to the studies of Xie et al [ 24 ] and Wu et al [ 25 ], during A-TIG welding with activating flux, the increase of penetration depth is mainly due to the influence of surface tension. Furthermore, the positive and negative temperature gradient has a great impact on the depth of the molten pool.…”
Section: Resultsmentioning
confidence: 99%
“…However, the effect of nucleant particles on the Mg welds’ grain structure is not extensively studied yet. It is shown that the addition of SiC nano-particles to the flux in activating flux GTAW process can results in some grain refining in the FZ [87, 88]. It is of note that the pre-existing nucleant particles can induce grain refining during solidification.…”
Section: Grain Structure Of the Fusion Zone: Columnar-to-equiaxed Tra...mentioning
confidence: 99%
“…They go on to treat this problem theoretically using the type of heat and fluid flow models that are typical in fusion welding 8,9 ; indeed, the redistribution of non-melting particles is a favourite topic in the welding of metal matrix composites. 10 Additive manufacturing can be used to create structures that are otherwise impossible or nearly impossible to make using traditional technologies. One example is the so-called lattice or cell structures of interconnected struts.…”
mentioning
confidence: 99%
“…They go on to treat this problem theoretically using the type of heat and fluid flow models that are typical in fusion welding 8,9 ; indeed, the redistribution of non-melting particles is a favourite topic in the welding of metal matrix composites. 10…”
mentioning
confidence: 99%